Transcriptome analysis revealed the mechanism of skeletal muscle growth and development in different hybrid sheep - Mengyu Lou; Sihuan Zhang; Wangxin Yang; Shuang Li; Hongguo Cao; Zijun Zhang; Yinghui Ling (Animal Bioscience)
Objective This study aimed to analyze the molecular mechanism of heterosis in East Friesian sheep×Hu sheep (EH) hybrid sheep and Suffolk×EH (SHE) hybrid sheep (Ovis aries). Methods In this research, the growth performance data of Hu sheep (H), EH and SHE from birth to 8 months of age were analyzed. Three 8-month-old sheep of each of the three strains (9 sheep in total) were chosen and their longissimus dorsi muscles were collected for transcriptome sequencing. We verified the expression of seven differentially expressed genes (DEGs) by real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR). Results The results showed: (1) body weight and chest circumference of EH were significantly greater than H (p<0.05), except at 4 months of age. Body weight and chest circumference of SHE was significantly higher than EH (p<0.05), except at 6 months of age. (2) 310 DEGs were screened in the EH and H, gene ontology and Kyoto encyclopedia of genes and genomes showed DEGs were mainly concentrate on the categories of actin cytoskeleton, calcium binding, cGMP-PKG and mitogen-activated protein kinase (MAPK) signaling pathway, which correlating the development of skeletal muscle and energy metabolism. 329 DEGs were screened in the SHE and EH. DEGs were mainly enriched in extracellular matrix-receptor interactions and cell adhesion molecules. (3) Protein–protein interaction screening yielded five (MYL2, TNNI1, TNNI3, MYH11, TNNC1) and three (SOX10, COL2A1, MPZ) pivotal DEGs regulating muscle development in EH and SHE. (4) RT-qPCR test results were consistent with transcriptome sequencing. Conclusion This study provides candidate genes for improving sheep growth traits. It provides a theoretical basis for analyzing the mechanism of muscle development in crossbred sheep.